Toxicity of polyethylene microplastics combined with medroxyprogesterone on photosynthetic pigments of Lemna minor - Martins, Thaís Fabiane Gomes [UNESP]; Rani-Borges, Bárbara; Queiroz, Lucas Gonçalves; de Souza, Karen Ferreira [UNESP]; Pompêo, Marcelo (My University, 2024)
Similar to microplastics (MPs), pharmaceuticals are recognized as emerging contaminants. In the environment, macrophytes experience simultaneous exposure to a mixture of these compounds. This study aimed to assess the impact of low-density polyethylene MPs (40–190 µm) and medroxyprogesterone acetate (DMPA; synthetic hormone) to determine the toxic effects on Lemna minor. A chronic assay of 168 h was conducted to expose macrophytes to two concentrations of each pollutant: MPs at 0.5 mg L−1 and 1.0 mg L−1, and DMPA at 26 ng L−1 and 26 µg L−1. The concentrations were evaluated both individually and in specific combinations, between both concentrations of MPs and DMPA, resulting in eight treatments, in addition to a negative control containing only plants and culture medium. The exposure effects were analyzed through chlorophyll a and b levels, carotenoids, frond number, and adhesion of MPs. MPs and DMPA did not show a significant impact on the specific growth rate or frond number of the macrophyte. Nonetheless, a deleterious effect on chlorophyll b content was observed in all treatments, in relation to the control. Combinations of MPs and DMPA significantly reduced these pigments, indicating stress caused by exposure to the drug. The number of adhered particles was higher on the roots compared to the fronds, suggesting specific adhesion of MPs to L. minor. This phenomenon underscores the potential role of plants as a pathway for the entry of MPs into food chains, since aquatic plants act as sinks for MPs in the environment. On the other hand, the substantial interaction of MPs with plants suggests a potential application in phytostabilization and eventually for the removal of MPs from the environment. Based on our findings, it is plausible to assert that vascular plants play a substantial role in the dynamics and fate of MPs within aquatic ecosystems.
Keywords: Aquatic plants; Emerging contaminants; Endocrine disruptors; Freshwater; Lemna minor